Evolution of Alfvén Waves in the Solar Wind. II. Broadband Driver - Khaled Alielden; Yeghiazar Taroyan (The Astrophysical Journal)
The propagation of azimuthal Alfvén waves and their interaction with the solar wind are investigated using a 2.5D magnetohydrodynamic model that incorporates the effects of optically thin radiation, as well as collisional and collisionless thermal conduction. The background plasma forms a dipole field that is extended into a helmet streamer by the solar wind, with slow wind near the equator and fast wind at mid- and high latitudes. Alfvénic wave trains, localized at random heliographic latitudes, are launched from the coronal base with a moderate amplitude of 9 km s ^−1 across a wide range of frequencies. Experiments with 100 and 200 events are carried out, resulting in the formation of a cavity where the waves are trapped. The cavity expands or contracts based on the dominant driver period, with longer-period waves setting up larger cavities. A distinctive feature of the cavity is the formation of large-amplitude backward waves that provide an additional push to the solar wind plasma at mid- and high latitudes through the ponderomotive force. We find that episodic and localized wave trains are more efficient at heating and accelerating solar wind plasma compared to continuous monochromatic waves uniformly launched from all heliographic latitudes. Increasing the number of wave events results in enhanced acceleration and heating of the solar wind plasma, as well as suppression of plasmoid breakup events in the equatorial plasma sheet.